The concept of alternative tourism and the study of the potential for wine tourism in Azerbaijan - Huseynli Nazim Intigam; Purhani Hasan Safar; Kabulov Ilyas (BIO Web of Conferences)
Alternative tourism has gained considerable attention in recent years as travelers seek unique and authentic experiences outside of traditional tourist destinations. One form of alternative tourism is enotourism, which focuses on the exploration of wine and the culture surrounding it. Wine tourism represents a growing niche within the broader field of alternative tourism, attracting people passionate about wine, culture, and sustainable travel. Alternative tourism aims to provide authentic and meaningful experiences, often involving smaller, less-visited destinations or unconventional activities. The main goal is to move away from standard tourism by encouraging sustainability, cultural exchange, and deeper connections between travelers and the places they visit.